2013
DOI: 10.1016/j.jpeds.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Neonates Undergoing Cardiac Operations: Relationship to Cardiopulmonary Bypass and Association with Outcomes

Abstract: Objectives To determine the incidence of vitamin D deficiency in neonates with congenital heart disease and whether differences exist by race. In addition, we determined the effect of cardiopulmonary bypass on vitamin D levels, and explored associations between 25-hydroxyvitamin D [25(OH)D] levels and postoperative outcomes. Study design A secondary analysis of a prospective randomized controlled trial in 70 neonates undergoing cardiac surgery was performed. 25(OH)D levels were collected in the operating roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 22 publications
1
31
1
4
Order By: Relevance
“…We know that off the pump technique is more often used in Europe then USA, which have significant effect on vitamin D concentrations. Similarly another study in neonates couldn’t demonstrate difference in outcomes other than vasopressor usage [30]. We were unable to demonstrate any difference in vasopressor usage, which may be result of very different patient populations.…”
Section: Discussioncontrasting
confidence: 65%
“…We know that off the pump technique is more often used in Europe then USA, which have significant effect on vitamin D concentrations. Similarly another study in neonates couldn’t demonstrate difference in outcomes other than vasopressor usage [30]. We were unable to demonstrate any difference in vasopressor usage, which may be result of very different patient populations.…”
Section: Discussioncontrasting
confidence: 65%
“…Graham et al 41 in their study observed that CPB did not have any effect on serum vitD levels in neonates postcardiac surgery and 84% of children have vitD deficiency from preoperative period itself. In our study, the control group followed the same pattern as shown by Graham et al 41 whereas the study group followed the pattern found in the studies published by others like Riad Abou et al, 39 McNally et al, 40 and Krishnan et al 42 One interesting finding was noticed in ►Table 6 the presurgery vitD levels of the Graham et al 41 study and the control group of our study corresponded to severe vitD deficiency, and their post CPB levels increased (though statistically insignificant) instead of decreasing contray to the findings from other three studies plus children in our study group where post CPB vitD level decreased significantly. Even though we cannot reach any conclusion as to why the serum vitD levels behave differently to CPB and acute hemodilution at different body levels of deficiency, we propose that it could be related to the multiple factors that control the serum vitD levels such as serum PTH, fibroblast growth factor (FGF) 23 levels, calcium levels, the distribution between the free and bound vitD levels in serum, and so forth.…”
Section: Discussionmentioning
confidence: 91%
“…42 A recent randomized placebo control trial by Shedeed et al of vitD supplementation in 80 infants with congestive heart failure was reported in which infants receiving vitD supplementation had greater improvements in clinical symptoms and echocardiographic measurements of ventricular size and function. 43 Shedeed et al, 43 McNally et al, 40 and Graham et al 41 noticed a reduced requirement of ionotropic support, fluid requirements, and short duration of mechanical ventilation among those with a higher serum vitD levels postoperatively. On the contrary, Lucidarme et al 18 and Rippel et al 37 did not find any correlation between serum vitD levels and the various prognostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to 2012, little attention was paid to vitamin D status during pediatric critical illness, with only three small studies reporting 25OHD levels on a total of 88 children. 39,74,75 Since 2012 there have been 10 observational studies evaluating vitamin D status in general PICU populations, [76][77][78][79][80][81][82][83][84][85] two focused on postoperative congenital heart disease (CHD), 86,87 and a pilot study of high-dose vitamin D in children with burns. 88 The 10 observational PICU studies originate from six countries and evaluate 2,000 children.…”
Section: Prevalence Of Vitamin D Deficiency In Picu Vitamin D Deficiementioning
confidence: 99%